Association of Depression and Anxiety with Shoulder Pain and Disability Index in Adhesive Capsulitis - Saba Nawaz, Syed Ali Hussain, Mubin Mustafa Kiyani, Rabia Afzal, Nouman Khan, Muhammad Umer Iqbal (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Impingement syndrome is a disorder of unknown etiology in which the restriction of shoulder movements is the result of inflammation of shoulder joint capsule and its ligaments. Aim: To explore relationship of depression and anxiety among Patients of Adhesive Capsulitis, and correlation of despair and nervousness with shoulder pain and disability index in Adhesive Capsulitis. Methodology: A correlational study was conducted in which 280 patients of both genders from different Hospitals were taken. A Questionnaire examined the association of depression and anxiety and determine the rate of Shoulder pain and Disability index in Frozen Shoulder patients. The Shoulder pain and Disability index scale and Hospital Anxiety and Depression Scale were also included in this study. SPSS v.26 analyzed the data. Mean±SD presented quantitative variables. Results: Out of 280 classified as diagnosed patients of Adhesive capsulitis in correlational study with mean and standard deviation of age is 49.75±8.19, Among 280, 33.9% were males and 66.1% were females. This study enumerates correlation between SPADI and HADS-A and between SPADI and HADS-D and the correlation is significant at the 0.01 level(2-tailed). Of the 280 FS patients, 62.5% had a high risk of anxiety and 37.5% were without anxiety. Conclusion: It was concluded in our study that there is strong association of depression and anxiety with Shoulder pain and Disability index in Adhesive Capsulitis. Keywords: Frozen Shoulder, SPADI, HADS and Depression.